The status of cryptococcosis in Latin America - Firacative, Carolina (2018)
Cryptococcosis is a life-threatening fungal infection caused by the encapsulated yeasts Cryptococcus neoformans and C. gattii, acquired from the environment. In Latin America, as occurring worldwide, C. neoformans causes more than 90% of the cases of cryptococcosis, affecting predominantly patients with HIV, while C. gattii generally affects otherwise healthy individuals. In this region, cryptococcal meningitis is the most common presentation, with amphotericin B and fluconazole being the antifungal drugs of choice. Avian droppings are the predominant environmental reservoir of C. neoformans, while C. gattii is associated with several arboreal species. Importantly, C. gattii has a high prevalence in Latin America and has been proposed to be the likely origin of some C. gattii populations in North America. Thus, in the recent years, significant progress has been made with the study of the basic biology and laboratory identification of cryptococcal strains, in understanding their ecology, population genetics, host-pathogen interactions, and the clinical epidemiology of this important mycosis in Latin America.